Chronology of gypsum dunes at Knolls, Utah: refining OSL techniques and timing of Holocene eolian processes - Fitzgerald, Victoria Teresa (Kansas State University, 2019)
This study examines eolian samples from post-Lake Bonneville gypsum dunes in Knolls, UT, primarily to determine suitability of optically stimulated luminescence (OSL) dating protocols for gypsum geochronology. Sedimentologists often rely on proxies to understand geologic timescales, OSL may eliminate that need in environments with gypsum. Using OSL we aimed to identify the ages of punctuated climatic events that are linked to deposition of the gypsum rich dunes found in the study area. To accomplish this pursuit, systematic research of gypsum preparation protocols were required. Multiple experiments were undertaken to assess the effectiveness of mineral isolation and etching. Knowledge of gypsum behavior is of particular interest, as it is found in both lacustrine and marine environments and is typically less soluble than other evaporites found in both settings, such as sodium chloride. Gypsum has also been observed at several hundred meters water depth in the alkaline environment of the Arctic Ocean. Additionally, gypsum sand grains are accessible to researchers in geomorphic features like unconsolidated to semi-consolidated dunes, making them easier to sample for OSL analyses than gypsum or quartz found in an outcrop. Sampling strategy can be quickly determined for dunes that are exposed on all sides. The focus of this study seeks to resolve discrepancies observed in the small body of literature on gypsum as an OSL chronometer. Relatively homogenous eolian gypsum sand grain samples with grain sizes ranging from <63 μm to >250 μm from two adjacent paleodunes (KNP-A and KNP-B) and one coppice dune (CD-5) were used to determine best preparation practices and identify if punctuated climatic events during the Holocene could be detected using gypsum. The sample site was selected for a case study on OSL dating techniques because previous work has constrained the maximum age of post-Lake Bonneville dune formation (~12 ka BP). Preparation protocols, independently checked using various methods, were selected with minimal mineralogical impact and OSL sensitivity considerations in mind. Bulk composition and mineralogy of the sediment at various steps in sample preparation have been analyzed using X-Ray Diffraction, bulk elemental extraction, particle size analysis, Scanning Electron Microscopy and binocular microscopy. Etching experiments indicate that an air-dried, dry-sieved, and gypsum-rich fraction (90-125 μm) can be effectively isolated and etched in ~36 wt % HCl for 40 minutes. Of the various OSL measurement protocols attempted, we confirmed a modified single-aliquot regenerative-dose protocol produces detectable luminescence signals and equivalent doses (Dₑ) that are usable in age calculations. Age results are likely to be underestimated by approximately 0.5-0.8 ka, based on comparison to a single quartz OSL sample (KNP-A1) with an age of 2.2 ka and it’s equivalent gypsum sample of 1.4 ka. This is the oldest age sampled from the stratigraphically lowest section of either KNP-A or KNP-B. Samples from KNP-B identify this smaller dune was deposited after KNP-A began developing. Age results from the stratigraphically lowest sample collected, KNP-B1, indicate deposition occurred at 0.88 ka. The active coppice dune (CD-5) gypsum OSL age is 0.09 ka. This study recommends further investigation into why the apparent discrepancy between gypsum and quartz OSL chronology exists.
Keywords: Gypsum; Optically stimulated luminescence; Holocene; Eolian dunes; Great Salt Lake Desert; Geochronology